2013
DOI: 10.4322/rca.2013.048
|View full text |Cite
|
Sign up to set email alerts
|

Plantio cruzado na cultura da soja utilizando uma cultivar de hábito de crescimento indeterminado

Abstract: RESUMO: O arranjo espacial de plantas afeta o aproveitamento de luz, água e nutrientes, podendo refletir na produção de fitomassa e na produtividade de grãos. Em razão de a soja apresentar alta plasticidade fenotípica, novos arranjos espaciais de plantas vêm sendo avaliados, a fim de aumentar a produtividade da cultura, como o plantio cruzado. O objetivo deste trabalho foi avaliar o crescimento e a produtividade de grãos da cultivar de soja de hábito indeterminado BRS 359 RR, em diferentes arranjos espaciais d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1
35

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 12 publications
4
45
1
35
Order By: Relevance
“…The thousand-grain weight was not affected by the evaluated treatments, corroborating results found in the literature (Procópio et al, 2013;2014), where Bruns (2011) concluded that the row type (twin or single row) or seeding…”
Section: Bsupporting
confidence: 77%
“…The thousand-grain weight was not affected by the evaluated treatments, corroborating results found in the literature (Procópio et al, 2013;2014), where Bruns (2011) concluded that the row type (twin or single row) or seeding…”
Section: Bsupporting
confidence: 77%
“…On the other hand, the leaf/stem dry matter ratio in the V5 stage was lower at the highest densities in both seasons, indicating that the increase in intraspecific competition promoted lower allocation of photoassimilates in the leaves, in detriment of the stem; hence, plant density significantly alters the structure of soybean canopy. At low densities, soybean plants form higher amount of leaves in relation to the stem, to intercept the light available in the community of plants, which occurs due to the decrease in the competition between plants for water, light and nutrients (Procópio et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In the seasons of 2013/14 and 2014/15, there were reductions of approximately 0.011 and 0.014 branches plant -1 for every thousand plants ha -1 of increment in plant density. According to Procópio et al (2013), the increase in branch number and size constitutes one of the main mechanisms that explain the high phenotypic plasticity of soybean in response to variations in plant density.…”
Section: Resultsmentioning
confidence: 99%
“…Plant density affects intraspecific competition for water, light and nutrients and may alter plant architecture, the use of environmental resources and phytosanitary management (Procópio et al 2013). Thus, density adjustment allows yield increments, with rationalization of the cost of seeds, and does not involve the use of new technology .…”
Section: Introductionmentioning
confidence: 99%